Quest for Chirality in 107Ag - 贺创业 张彪 竺礼华 吴晓光 孙慧斌 郑云 于蓓蓓 王烈林 李广生 姚顺和 徐川 王建国 顾龙 (等离子体科学和技术：英文版, 2012)
High spin states in 107Ag have been studied via the 100Mo （11B, 4n） 107Ag reaction at a beam energy of 60 MeV on the HI-13 tandem accelerator at the China Institute of Atomic Energy. By analyzing the gamma-gamma coincidence and their DCO ratios, a new level scheme of 107Ag is presented. The structures for the newly constructed bands are briefly discussed and tentatively assigned to be chiral doublet bands.